A violência da escola e o fracasso escolar - Cortez, Carla Magalhães [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
For Charlot (2002), there are three types of violence present in the school; violence in schools, violence at school and school violence. Violence in school is a violence that is not on the nature of the institution, is produced within the same, but could be present in any other space; violence at school is violence produced by the students to school institution through heritage depredation and violents atitudes for those who represent the institution; and school violence is the violence of the institution and those who represent it, shown by the school environment organization. This work intends to analyze the school violence as one of the responsible for school failure, through bibliographical research, the intend is to portray how the school violence is intrinsically related to the failure of the school and not to the failure of the student, which most often is blamed for the failure of the school outcome. Our aim is to analyze and understand how the issue of school violence is theoretically treated and the movie's relation to education. Our study will be based on authors such as Charlot, Althusser, Passeron, Bourdieu and Motta among others, will use the qualitative approach

Para Charlot (2002), há três tipos de violência presentes na escola; a violência na escola, a violência à escola e a violência da escola. A violência na escola é uma violência que não está ligada a natureza da instituição, se produz dentro da mesma, contudo poderia estar presente em qualquer outro espaço, a violência à escola é violência produzida pelos alunos á instituição escolar através de depredação do patrimônio e atitudes violentas em relação aos que representam a instituição e a violência da escola é a violência da instituição e dos que a representam se mostra através da própria organização do espaço escolar. O presente trabalho tem a intenção de analisar a violência da escola como uma das responsáveis pelo fracasso escolar, através de pesquisa bibliográfica pretende-se retratar como a violência da escola está intrinsecamente relacionada ao fracasso da escola e não ao fracasso do aluno que na maioria das vezes é responsabilizado pelo insucesso do desfecho escolar. Nosso objetivo é analisar e compreender como a questão da violência da escola é tratada teoricamente e a relação do cinema com a educação. Nosso estudo será fundamentado em autores como Charlot, Althusser, Passeron, Bourdieu e Motta dentre outros, utilizará a abordagem qualitativa
Keywords: Violencia escolar; Burocracia; Fracasso escolar; Educação e Estado; Cinema - Aspectos sociais; School violence